Pengembangan Media Monopoli Menggunakan Model Problem Based Learning Pembelajaran IPA Kelas III di SDN Kampung Melayu III - Melanis, Melanis; Fadilah, Ahmad Arif; Oktrifianty, Erdhita (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2023)
Education plays an important role in improving the quality of Human Resources and aims to make people who are virtuous, knowledgeable, and dignified. The implementation of science learning at SDN Kampung Melayu III is still less attractive because it only uses media such as textbooks, modules, and worksheets, so there is a need for the development of learning media to improve learning outcomes. This study uses the R&D method to produce new products or improve existing ones by considering certain aspects. Data collection techniques used are interviews, questionnaires, tests, and documentation, conducted in October 2022 involving subject matter and media experts, third-grade teachers, as well as small and large groups of class III A at SDN Kampung Melayu III, Teluknaga District, Tangerang Regency. This study develops monopoly-based problem-based learning science learning media. This study includes six validation stages and three field trial stages, with results showing that monopoly media is effective in improving students' ability in science learning and can be used as a fun learning resource. In science learning at SDN Kampung Melayu III, the use of monopoly media with problem-based learning models has been proven to significantly improve student learning outcomes and is suitable because it can help students solve problems critically and develop problem-solving skills.